Evolution of the supercritical extraction of oilseeds matrix cultivated in brasil: a review (International Seven Journal of Health Research, 2023)
The diversity of oil seeds in in Brazil turns the country into a very important role player in the production of raw material and vegetable plant products such as oil and extracts products. The processes of the extraction of oil with supercritical fluids are potential alternative methods for obtaining vegetable oil as alternative processes for substituting the traditional extraction methods such as manual pressing and extraction with solvent. This method presents advantages such as fast rate of reaction, flexibility of raw material, production efficiency and ecological benefits. This article presents a review covering actual supercritical extraction scenarios of vegetable oil from raw materials found in abundance in Brazil. The review presents a discussion about the influence of the principal operation perimeters on the extraction yield, modes of operation and the proximity with the industrial application, in a huge compilation of works in the period between 2000 - 2016, in other to unravel these indicators and their trends.